Latent tuberculosis infection screening and treatment in congregate settings (TB FREE COREA): protocol for a prospective observational study in Korea. Issue 2 (18th February 2020) - Min, Jinsoo; Kim, Hyung Woo; Stagg, Helen R; Lipman, Marc; Rangaka, Molebogeng X; Myong, Jun-Pyo; Yim, Hyeon Woo; Lim, Jeong Uk; Lee, Yunhee; Koo, Hyeon-Kyoung; Lee, Sung-Soon; Park, Jae Seuk; et al.
Abstract : Introduction: South Korea regards tuberculosis (TB) incidence in congregate settings as a serious problem. To this end, systematic latent TB infection (LTBI) diagnosis and treatment were provided to approximately 1.2 million individuals in high-risk congregate settings. Methods and analysis: We designed a prospective cohort study of individuals tested for LTBI, based on the data collected on all persons screened for LTBI as part of the 2017 congregate settings programme in South Korea. Four types of databases are kept: LTBI screening database (personal information and LTBI test results), national health information (NHI) database (socio-demographic data and comorbidities), public healthcare information system (PHIS) database, and the Korean national TB surveillance system database (TB outcomes). Information regarding LTBI treatment at private hospitals and public health centres is collected from NHI and PHIS databases, respectively. The screening data are cleaned, duplicates are removed, and, where appropriate, re-coded to analyse specific exposures and outcomes. The primary objective is to compare the number of active TB cases prevented within 2 years between participants undergoing treatment and not undergoing treatment in the LTBI screening programme in congregate settings. Cascade of care for LTBI diagnosis and treatment will be evaluated among those with a positive LTBI test result. A Cox proportional hazards model will be applied to determine the risk factors for developing active TB. Ethics and dissemination: The protocol is approved by the institutional review boards of Incheon St. Mary's Hospital, the Catholic University of Korea. Study results will be disseminated through peer-reviewed journals and conference presentations. Trial registration number: KCT0003905